2019
DOI: 10.2147/cmar.s213931
|View full text |Cite
|
Sign up to set email alerts
|

<p>The synergistic antileukemic effects of eltrombopag and decitabine in myeloid leukemia cells</p>

Abstract: BackgroundHypomethylating agents (HMAs), such as decitabine (DAC), are currently used as first-line therapy for patients with high-risk myelodysplastic syndromes (MDS) and acute myelogenous leukemia (AML) not eligible for standard chemotherapies. Exacerbation of thrombocytopenia is one of the prevalent complications after HMA treatment. Eltrombopag (EP), an oral thrombopoietin receptor agonist, can efficiently stimulate megakaryopoiesis and elevate platelet counts in MDS/AML patients. However, the significance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 35 publications
3
12
0
Order By: Relevance
“…Instead, we identified that the growth inhibitory effect of eltrombopag is due, in part, to the iron chelation properties of the drug, which provides further support for our previous work that identified iron chelator drugs as a unique vulnerability of Ewing sarcoma tumor in vitro and in vivo [7]. Notably, eltrombopag has also been reported to target additional cancer types, including leukemia and hepatocellular carcinoma, via an iron chelation mechanism [12,13,55].…”
Section: Discussionsupporting
confidence: 81%
“…Instead, we identified that the growth inhibitory effect of eltrombopag is due, in part, to the iron chelation properties of the drug, which provides further support for our previous work that identified iron chelator drugs as a unique vulnerability of Ewing sarcoma tumor in vitro and in vivo [7]. Notably, eltrombopag has also been reported to target additional cancer types, including leukemia and hepatocellular carcinoma, via an iron chelation mechanism [12,13,55].…”
Section: Discussionsupporting
confidence: 81%
“…This controversial aspect on iron overload management could depend on the considered cell type and health condition. As regards cell cycle progression, we observed a block in S phase after cytarabine administration in THP-1 cells, as also reported for decitabine, another chemotherapy drug currently used in AML not eligible for standard protocols [37]. But, when we combined it with ELT, the arrest shifted in G0/G1 phase, consistently with the already documented effects of ELT used alone [37,40].…”
Section: Figure 5: Effect Of 48-hour Treatments On Proliferation Nfkb Protein Expression Level In Thp-1 Cell Line Was Determined Bysupporting
confidence: 88%
“…As regards cell cycle progression, we observed a block in S phase after cytarabine administration in THP-1 cells, as also reported for decitabine, another chemotherapy drug currently used in AML not eligible for standard protocols [37]. But, when we combined it with ELT, the arrest shifted in G0/G1 phase, consistently with the already documented effects of ELT used alone [37,40]. Several authors demonstrated that iron chelators reduce cyclin-dependent kinase 2 (CDK2) activity [41][42][43], a protein normally responsible for cell cycle progression from G0/G1 phase to S one.…”
Section: Figure 5: Effect Of 48-hour Treatments On Proliferation Nfkb Protein Expression Level In Thp-1 Cell Line Was Determined Bysupporting
confidence: 85%
See 2 more Smart Citations